Encountering the "Muslim": Guantánamo Bay, Detainees, and Apprehensions of Violence. Issue 2 (August 2019) - Rochelle, Safiyah
Abstract: This article focuses on the underlying sensorial entanglements that linger in spaces and moments of encounter between state violence and its targets. It argues that in Guantánamo Bay, these entanglements become routed through the bodies of the camp's detainees, and they rely upon a particular reading of religion as being borne by bodies in such ways as to necessitate the use of specific techniques of detention and incapacitation. This discussion is framed using the notion of "apprehension, " in its affective and material forms, wherein perception, dread, and physical encounters in the camp unfold within a framing of Muslims as ontologically and materially distinct, and as being embodied in particular ways. In these processes of apprehension, the techniques and logics of violence deployed in the war on terror become further legitimated, and work reflexively to shape the ways in which the Muslim is known, encountered, and met with violence. Résumé: Cet article se penche sur les interactions sensorielles fondamentales qui persistent dans les espaces et les moments de rencontre entre la violence étatique et ses cibles. Cet article suggère qu'au camp de Guantánamo Bay, ces interactions sont acheminées à travers le corps des détenus et que celles-ci reposent sur une interprétation particulière de la religion comme étant portée par les corps de manière à nécessiter l'utilisation de techniques spécifiques de détention et de neutralisation. Cette discussion s'appuie sur la notion d'« appréhension » dans ses formes affectives et matérielles. Dans ce camp, la perception, la peur et les contacts physiques se présentent en effet dans un contexte où les personnes musulmanes sont considérées comme ontologiquement et matériellement distinctes et comme étant incarnées d'une manière particulière. Dans ces processus d'appréhension, les techniques et les logiques de violence déployées dans la guerre contre le terrorisme trouvent une légitimité et agissent de manière réflexive afin de façonner la manière dont on connaît les Musulmans, entre en contact avec eux et les réprime.